A sensor network based virtual beam-like structure method for fault diagnosis and monitoring of complex structures with Improved Bacterial Optimization. (1st February 2017) - Wang, H.; Jing, X.J.
Abstract: This paper proposes a novel method for the fault diagnosis of complex structures based on an optimized virtual beam-like structure approach. A complex structure can be regarded as a combination of numerous virtual beam-like structures considering the vibration transmission path from vibration sources to each sensor. The structural 'virtual beam' consists of a sensor chain automatically obtained by an Improved Bacterial Optimization Algorithm (IBOA). The biologically inspired optimization method (i.e. IBOA) is proposed for solving the discrete optimization problem associated with the selection of the optimal virtual beam for fault diagnosis. This novel virtual beam-like-structure approach needs less or little prior knowledge. Neither does it require stationary response data, nor is it confined to a specific structure design. It is easy to implement within a sensor network attached to the monitored structure. The proposed fault diagnosis method has been tested on the detection of loosening screws located at varying positions in a real satellite-like model. Compared with empirical methods, the proposed virtual beam-like structure method has proved to be very effective and more reliable for fault localization. Highlights: A novel method for fault detection of complex structures using an optimized virtual beam-like structure approach. A 'virtual beam' consists of a sensor chain automatically obtained by an Improved Bacterial Optimization Algorithm from the sensor network. The method needs less or little prior knowledge of the faults, does not require stationary response data, and is not applicable only to a specific structure. The proposed fault diagnosis method is extensively tested in a real satellite-like model.